PENGEMBANGAN VARIAN PRODUK DENGAN PELATIHAN FORMULASI KRIM KEFIR SUSU KAMBING SEBAGAI PENCERAH KULIT - Uswatun Chasanah; Dyah Rahmasari (Universitas Muhammadiyah Tapanuli Selatan, 2021)
The kefir of goat's milk has good benefits for skin health. There are goat milk kefir creams on the market, but tutorials to make cream of goat's milk kefir are not available on social media, even though it useful by the goat milk producer who wants to develop product variations. Training for goat's milk kefir cream formulation had done, partner of this activity is a goat milk producing community. This activity begins with a theoretical and technical explanation of the making of goat's milk kefir cream then continues with training activities, and video tutorials were uploaded to social media, too. It has been an increase in the knowledge and skills of the Partners. This activity is an inspiration for Partners to add product variants, especially making kefir cream.